2012
DOI: 10.1371/journal.pone.0050704
|View full text |Cite
|
Sign up to set email alerts
|

Mucin Deficiency Causes Functional and Structural Changes of the Ocular Surface

Abstract: MUC5AC is the most abundant gel-forming mucin in the ocular system. However, the specific function is unknown. In the present study, a Muc5ac knockout (KO) mouse model was subject to various physiological measurements as compared to its wide-type (WT) control. Interestingly, when KO mice were compared to WT mice, the mean tear break up time (TBUT) values were significantly lower and corneal fluorescein staining scores were significantly higher. But the tear volume was not changed. Despite the lack of Muc5ac ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 26 publications
3
36
1
Order By: Relevance
“…Using the same Muc5ac null mice, as well as mice null for Muc5b, we examined the ocular surface for the presence of a dry eye phenotype. Results from our study differed greatly from those reported by Floyd et al, 14 as we found no major ocular surface phenotype in the Muc5ac null mice; in fact, no identifiable ocular surface phenotype was observed, even after exposure to desiccating environmental stress. Moreover, our results showed no ocular surface phenotype present in the Muc5b null mice, either before or following exposure to a dry environment in the controlled environment chamber (CEC).…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…Using the same Muc5ac null mice, as well as mice null for Muc5b, we examined the ocular surface for the presence of a dry eye phenotype. Results from our study differed greatly from those reported by Floyd et al, 14 as we found no major ocular surface phenotype in the Muc5ac null mice; in fact, no identifiable ocular surface phenotype was observed, even after exposure to desiccating environmental stress. Moreover, our results showed no ocular surface phenotype present in the Muc5b null mice, either before or following exposure to a dry environment in the controlled environment chamber (CEC).…”
contrasting
confidence: 99%
“…A recently published manuscript using the same Muc5ac null mice as those used in this study reported that lack of the major secretory mucin Muc5ac caused significant functional and structural changes to the ocular surface in these mice, creating an ocular surface phenotype similar to that observed in dry eye syndrome. 14 While there are many major discrepancies between our data and those reported by Floyd et al, 14 several findings are consistent between the investigations. Neither study found a change in the aqueous tear volume of Muc5ac null mice compared to that of agematched wild-type control mice.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Interestingly, Muc5ac-deficient mice have less lung inflammation and pulmonary edema following ventilator-induced lung injury due to reduced pulmonary neutrophil trafficking (Koeppen et al, 2012). These mice also develop symptoms of dry eye disease consistent with inadequate hydration of or protection of the ocular surface (Floyd et al, 2012). Further work is required in multiple tissues to establish the roles of secreted mucins in normal physiology.…”
Section: Secreted Mucins and Mucusmentioning
confidence: 99%